2018
DOI: 10.1148/radiol.2017171221
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Degree of Intestinal Fibrosis in Patients with Crohn Disease by Using Magnetization Transfer MR Imaging

Abstract: Purpose To evaluate the role of magnetization transfer (MT) magnetic resonance (MR) imaging for the characterization of intestinal fibrosis compared with contrast material-enhanced and diffusion-weighted MR imaging and its capability for differentiating fibrotic from inflammatory strictures in humans with Crohn disease (CD) by using surgical histopathologic analysis as the reference standard. Materials and Methods Institutional review board approval and informed consent were obtained for this prospective study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 101 publications
(102 citation statements)
references
References 20 publications
2
75
0
Order By: Relevance
“…However, the low performance in discriminating among none, mild, and moderate fibrosis might limit the use of delayed enhancement MRE. 1,124,127 Novel magnetic resonance (MR) techniques to detect fibrotic stricture include diffusion-weighted imaging (DWI)-MRE and magnetization transfer-MR (MT-MR). DWI can be completed quickly without intravenous contrast and provide a quantitative index, for example, apparent diffusion coefficient (ADC), which reflects the rate of water diffusion through the tissues.…”
Section: Complete Overlap Between Inflammation Andmentioning
confidence: 99%
“…However, the low performance in discriminating among none, mild, and moderate fibrosis might limit the use of delayed enhancement MRE. 1,124,127 Novel magnetic resonance (MR) techniques to detect fibrotic stricture include diffusion-weighted imaging (DWI)-MRE and magnetization transfer-MR (MT-MR). DWI can be completed quickly without intravenous contrast and provide a quantitative index, for example, apparent diffusion coefficient (ADC), which reflects the rate of water diffusion through the tissues.…”
Section: Complete Overlap Between Inflammation Andmentioning
confidence: 99%
“…20 Table 1 summarizes the main characteristics of novel imaging modalities that had been investigated to detect and quantify fibrosis in CD, whereas Table 2 provides the evidence obtained in studies testing the techniques against histopathology. [9][10][11][13][14][15][21][22][23][24][25] To date, all the evidence comes from single-center studies with relatively small samples. Before these noninvasive quantitative imaging biomarkers can be widely implemented, further multicenter large-scale studies are needed to establish cutoff values, test their reproducibility, and determine their degree of interobserver agreement.…”
Section: Use (Swe Strain Ratio Arfi)mentioning
confidence: 99%
“…The quantitative parameters of MTI (MTR and normalized MTR) were both reported to be capable of characterizing the severity of bowel fibrosis in animal or human CD (2,3,7,9). Our preliminary results and those of other studies showed that a higher MTR or normalized MTR of the thickened intestinal wall, similar to that of the muscle presenting the highest MTR in human tissue, indicated a higher fibrotic composition of the lesion (2,3,9). However, in clinical practice, sometimes a relatively higher MTR or normalized MTR might be observed in the normal intestinal wall, which may hinder interpretations of the result.…”
Section: Discussionmentioning
confidence: 99%
“…However, a low MTR may be detected in severely fibrotic bowel walls with a similarly low MTR of muscle in some cases due to individual differences. To facilitate the comparison between individual cases, the MTR of the affected bowel wall was divided by the MTR of the muscles on the same image to obtain a normalized MTR to minimize individual variation (3,9). This normalized MTR also showed a high accuracy in detecting and further stratifying bowel fibrosis in CD (9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation